Visceral versus somatic pain: an educational review of anatomy and clinical implications. Issue 7 (18th June 2021) - Boezaart, Andre P; Smith, Cameron R; Chembrovich, Svetlana; Zasimovich, Yury; Server, Anna; Morgan, Gwen; Theron, Andre; Booysen, Karin; Reina, Miguel A
Abstract : Somatic and visceral nociceptive signals travel via different pathways to reach the spinal cord. Additionally, signals regulating visceral blood flow and gastrointestinal tract (GIT) motility travel via efferent sympathetic nerves. To offer optimal pain relief and increase GIT motility and blood flow, we should interfere with all these pathways. These include the afferent nerves that travel with the sympathetic trunks, the somatic fibers that innervate the abdominal wall and part of the parietal peritoneum, and the sympathetic efferent fibers. All somatic and visceral afferent neural and sympathetic efferent pathways are effectively blocked by appropriately placed segmental thoracic epidural blocks (TEBs), whereas well-placed truncal fascial plane blocks evidently do not consistently block the afferent visceral neural pathways nor the sympathetic efferent nerves. It is generally accepted that it would be beneficial to counter the effects of the stress response on the GIT, therefore most enhanced recovery after surgery protocols involve TEB. The TEB failure rate, however, can be high, enticing practitioners to resort to truncal fascial plane blocks. In this educational article, we discuss the differences between visceral and somatic pain, their management and the clinical implications of these differences.